Does Foreign Aid Really Work? An Updated Assessment - Riddell, Roger C. (Social Science Research Network, 2014)
This paper draws widely from the book Does foreign aid really work?, b uilding on that discussion to provide an updated answer to the questio n based on recent evidence and contemporary debates on aid effectivene ss. It starts with a brief discussion (Section 2) of the question: ‘do es emergency aid work?’ This is important to the wider debate for two linked reasons. Firstly, the harshest critics of development aid are a ll supportive of emergency aid, with a number calling for its expansio n in spite of evidence of major weaknesses and failures. Secondly, the sharp historical distinction made between emergency and development a id is becoming increasingly strained, as more emergency aid is being u sed a year or more after emergencies strike to rebuild lives and resto re livelihoods, while more development aid is used to directly save li ves.The rest of the paper focuses exclusively on development aid. Sect ion 3 provides a rapid overview of the evidence of the impact of indiv idual aid projects, including those of Non-Governmental Organisations (NGOs). The picture is overwhelmingly positive: well over 75% of proje cts meet their immediate objectives and impact has improved, even thou gh sustaining benefits remains a challenge and there continue to be ai d failures. Section 4 reviews the evidence of the wider and long-term impact of aid at the sectoral and country level, including a brief dis cussion of academic studies on aid and growth. Though there are still major gaps in our knowledge, the quality of the data is improving. How ever, there is little firm, quantitative evidence to show the specific contribution that aid has made to help achieve the Millennium Develop ment Goals (MDGs), which are a central purpose of many current donor p rogrammes (Section 4.2). More widely, there is plenty of evidence to s uggest that aid has contributed positively to both growth and wider de velopment at the sector and country level, though some studies suggest aid has had little or no impact. Overall, the contribution that aid m akes to aggregate development is lower than the public has been led to believe (Sections 4.1, 4.3. and 4.4). Assessments of the overall impa ct of the aid provided by NGOs are rare, but a recent study suggests i t has been positive (Section 4.5). More attention is now given to the issues of corruption in aid. Although there is evidence of aid funds b eing used for corrupt purposes and of aid worsening corruption, on bal ance it remains a minor issue. Aid has had significant successes in he lping the poor affected by corruption (Section 4.6). The second half o f the paper shifts focus to the large gap between what aid has done an d what it might do. Section 5 discusses a range of inefficiencies with in and across the aid system and their costs in terms of reduced impac t, including the way aid is allocated, its growing complexity, and the volatility and unpredictability of aid flows (Section 5.1 and 5.2). T hese inefficiencies place in a different light the evidence of aid’s o verall positive impact. The paper looks at the different initiatives t hat have been mounted to begin to address these weaknesses and failure s, including the 2005 Paris Declaration, and discusses why donors have failed to honour the promises they have made to change the ways that they give aid.In Section 5.3, the paper argues that the most critical debate about whether aid works concerns the assessment of whether the short-term, immediate and extensive benefits that aid undoubtedly brin gs are outweighed by the direct and indirect systemic problems that it risks creating or accentuating. As increasingly over the last decade donors have channelled more of their aid into short-term, quick-impact projects, assessing the wider negative systemic effects of aid has be come even more important. Some recent studies suggest that aid’s syste mic problems are large and growing, narrowing the gap between aid’s ha rshest critics and broader analyses of aid impact. Against the backdro p of already too many proposals of how to make aid work better, Sectio n 6 lays out nine concrete proposals for doing this: deepening knowled ge of local contexts; ensuring short-term uses of aid are consistent w ith and supportive of long-term development, and that all aid is more closely related to overall recipient development goals and processes; helping build local capacities for recipients to be able to coordinate aid better; moving from rhetoric to reality in learning lessons from aid; using aid to help the poor in middle income countries; reducing v olatility in aid at the country level; encouraging budget support by a ddressing donor-country political concerns; and rethinking ways of com municating about aid. Section 7 concludes. It suggests that, paradoxic ally, aid’s impact may well have been harmed by focussing too narrowly on trying to make short-term aid work better, and that the main focus of attention needs to widen to assess how aid can contribute more to a recipient’s own development goals. Additionally, donors need to help build the capacity of developing countries and developing country sch olars to enable them to play a bigger role in helping to answer the qu estion of whether aid works; unsettling though their assessments may b e.